Adoption of Sustainable Supply Chain Enablers : A Construction Industry Perspective - Khan, Firdous Ahmad; Imran Khan, Mohd. (Prabandhan: Indian Journal of Management, 2023)
Organizations pledge to adhere to sustainability standards globally. The adherence to sustainability ensures businesses contribute to the country’s development, environment, and long-term societal values. Sustainable supply chain (SSC) has been receiving more focus from regulators, practitioners, and academicians nowadays. Among other industries, the building and construction industry has been accountable for using excessive resources and destroying the environment by producing pollution. The non-compliance to adopt sustainability creates barriers for the construction industry to implement SSC, which academia has given little attention to. The proposed research work is a critical study toward identifying SSC enablers in the construction industry and attempting to derive a causal relationship to evolve key enablers for SSC adoption based on hybrid MCDM methods. The novelty of the current work is the identification of key enablers in adopting SSC, and the interrelationship between enablers is of its first kind to be used for SSC. A case example was undertaken to find key enablers of sustainable procurement management in the construction supply chain to validate the proposed work. This study reveals that the obligation of an organization to adopt sustainable procurement management practices; government regulation to adopt sustainable procurement management practices; high incentive schemes for construction organizations in implementing sustainable procurement management practices; lower, middle, and top management involvement in adopting sustainable procurement practices; and sufficient checks and controls in adopting sustainable procurement management practices are the key enablers to be adopted by the businesses to achieve their sustainable goals.